Prying open the black box of causality: a causal mediation analysis test of procedural justice policing - Posch, Krisztian (2020)
Objectives: Review causal mediation analysis as a method for estimating and assessing direct and indirect effects. Re-examine a field experiment with an apparent implementation failure. Test procedural justice theory by examining to which extent procedural justice mediates the impact of contact with the police on police legitimacy and social identity. Methods: Data from a block-randomised controlled trial of procedural justice policing (the Scottish Community Engagement Trial) were analysed. All constructs were measured using surveys distributed during roadside police checks. Treatment implementation was assessed by analysing the treatment effect’s consistency and heterogeneity. Causal mediation analysis, which can derive the indirect effect even in the presence of a treatment–mediator interaction, was used as a versatile technique of effect decomposition. Sensitivity analysis was carried out to assess the robustness of the mediating role of procedural justice. Results: First, the treatment effect was fairly consistent and homogeneous, indicating that the treatment’s effect is attributable to the design. Second, there is evidence that procedural justice channels the treatment’s effect towards normative alignment (NIE = − 0.207), duty to obey (NIE = − 0.153), and social identity (NIE = − 0.052), all of which are moderately robust to unmeasured confounding (ρ = 0.3–0.6, LOVE = 0.5–0.7). Conclusions: The effect’s consistency and homogeneity should be examined in future block-randomised designs. Causal mediation analysis is a versatile tool that can salvage experiments with systematic yet ambiguous treatment effects by allowing researchers to “pry open” the black box of causality. The theoretical propositions of procedural justice policing were supported. Future studies are needed with more discernible causal mediation effects